The Impact of E-Procurement Implementation in Infrastructure Projects - Rizki, Alisia Ardita (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2019)
This paper aims to explore systematically about impact as well as facilitators and barriers of e-procurement implementation in the Ministry of Public Works and Housing. This study used qualitative approach and RE-AIM framework. The data were collected from semi-structured interviews and secondary data such as blueprint, strategic planning document, performance report, activities report, and financial report. The findings show that e-procurement implementation in Ministry of Public Works and Housing has reached the target of users, reduced cost and time, followed regulation, and become routine activity. Moreover, there are facilitators of the e-procurement implementation which are software integration, data management, IT infrastructure, and roll-out strategy. However, some barriers which are legal and administrative procedure, system security, and IT staff and skills, are found as barriers in implementing e-procurement